Plant Bioinspired Ecological Robotics - Frazier, P. Adrian; Jamone, Lorenzo; Althoefer, Kaspar; Calvo, Paco (Frontiers in Robotics and AI, 2020)
Plants move. But the nature of their movement differs dramatically from that of creatures that move their whole body from Point A to Point B. Plants grow to where they are going, and they extend themselves out and away from any one place. Bio-inspired robotics sometimes emulate plants’ growth-based movement, but growing is part of a broader system of movement guidance and control. We argue that ecological psychology’s conception of information and control and can simultaneously make sense of what it means for a plant to navigate its environment and provide a control scheme for the design of ecological plant-inspired robotics. In this effort, we will outline several control laws and give special consideration to the class of control laws identified by tau theory, such as time to contact.